Pendekatan Semantik dalam Taujîh Al-Mutasyâbih Al-Lafzhî: Studi Analitis atas Kitab Milâk Al-Ta’wîl Karya Ibnu Al-Zubair Al-Ghornâthî - Samsul Dani Aryanto; Muhammad Azizan Fitriana; Samsul Ariyadi (Indo-MathEdu Intellectuals Journal, 2026)
Studies on al-mutasyâbih al-lafzhî in Qur’anic scholarship have generally exhibited repetitive analytical patterns and limited engagement with underexplored classical works. This study aims to examine the method and systematic structure of taujîh al-mutasyâbih al-lafzhî in Milâk al-Ta’wîl by Ibn al-Zubair al-Ghornâthî, and to investigate the semantic implications derived through linguistic and munâsabah approaches. The research is motivated by long-standing scholarly debates concerning the meanings of repeated or lexically similar Qur’anic verses, ranging from views that generalize identical meanings to those asserting absolute semantic differences. Employing library research with a descriptive-analytical method, this study uses Milâk al-Ta’wîl as the primary source, supported by classical works of ‘ulûm al-Qur’ân and tafsir literature. The findings reveal that Milâk al-Ta’wîl represents a pioneering contribution to the discipline of taujîh al-mutasyâbihât al-lafzhiyyah, characterized by a thematic method, dialogical structure, and arrangement following the tartîb al-mushaf. The identified semantic implications not only offer interpretative variations but also function as mechanisms for integrating meanings among similar verses, demonstrating the precision of Qur’anic diction, and preventing perceptions of semantic contradiction. This study contributes an alternative analytical model for understanding al-mutasyâbih al-lafzhî in Qur’anic interpretation.